De novo genesis of enhancers in vertebrates - Eichenlaub, Michael P.; Ettwiller, Laurence (PLoS biology, 2011)
Whole genome duplication in teleost fish reveals that a few changes in non-regulatory genomic sequences are a source for generating new enhancers.